CYANOBACTERIA IN ANTARCTICA: A MULTIDISCIPLINARY STUDY - Micheli C.; Paperi A.; Buccioni B.; Pushparaj B.; CIANCHI, Maria Rossella (Association for the Sciences of Limnology and Oceanography, 2009)
Antarctic cyanobacteria biodiversity was investigated at various levels including the morphological, genetic and physiological aspects. Cyanobacteria were collected in Antarctica during the Austral Summer Cruise 2004; the strains were isolated from South polar lakes sediments, soil and liken associations and subsequently they were grown in laboratory conditions before to be analysed. The strains belong to the genera of Nostocales and Oscillatoriales were morphologically identified by microscopy. The fatty acid composition varied among the strains with a relatively high quantity of polyunsaturated fatty acid production. A first genetic investigation by RAPD markers was performed. Cyanobacteria strains were also identified by ITS and TrnL sequencing. Antarctic cyanobacteria diversity and their geographical distribution revealed their particular tolerance range to harsh environmental conditions. We confirm that the successful classification of cyanobacteria species requires the application of multiple taxonomic criteria